Infestation of the pumpkin caterpillar, diaphania indica saunders in cucurbits and its management. - Neena Lenin (Department of Agricultural Entomology, College of Agriculture, 2011)
Survey conducted in the Kalliyoor panchayath of Thiruvananthapuram district during 2009-2010 revealed the incidence of the pumpkin caterpillar, Diaphania indica Saunders in bitter gourd, snake gourd, cucumber and coccinia. The extent of infestation was high in bitter gourd, snake gourd and cucumber and low in coccinia. The infestation was significantly higher during the fruiting followed by the flowering and vegetative stages. Leaves and fruits of bitter gourd, snake gourd and coccinia were damaged by the pest. Only the leaves of cucumber were damaged. No significant differences were noted in the extent of infestation when more organic manures or more fertilizers were applied by the farmers. Similarly, the high and low doses of fertilizers applied also did not influence the extent of damage. The plant protection measures adopted by the farmers too had no significant effect on the extent of damage. The red amaranth (Amaranthus tricolor Linn.) and green amaranth (Amaranthus dubius L.) and the weed plants, the slender amaranthus (Amaranthus viridis L.) and bristly starbur (Acanthospermum hispidum DC.) were recorded as host plants of D. indica. The parasitoid Apanteles sp. was the only natural enemy recorded during the survey. Among the botanicals screened, annona seed extract 5%, neem oil garlic emulsion 2%, neem seed kernel extract 5%, Anosom 2ml l-1, Derisom 2ml l-1 and NeemAzal T/S 2ml l-1 resulted in high mortality of the caterpillars upto three days after treatment both when applied topically and released on treated leaves. The efficacy of Anosom 2ml l-1 extended to the seventh day when released on treated leaves. Topical application of spinosad 0.015%, flubendiamide 0.004%, profenophos 0.05%, diafenthiuron 0.02%, triazophos 0.05% and chlorpyriphos 50%+ cypermethrin 5% 0.05% resulted in 100 per cent mortality of the caterpillars one day after treatment. When released on treated leaves, flubendiamide 0.004% and spinosad 0.015% proved to be the better treatments, registering mortality of the pest upto 15 days after treatment. 80 Field evaluation with annona seed extract 5%, Anosom 2ml l-1, B. bassiana 2g l-1, B. thuringiensis 2g l-1, flubendiamide 0.004% spinosad 0.015% and carbaryl 0.15% indicated that flubendiamide 0.004% was the most effective, the reduction in the pest population being 60 per cent. Spinosad 0.015% and Anosom 2ml l-1 also resulted in significant reduction in the pest population, the extent of reduction being 46 and 43 per cent, respectively. Annona seed extract 5% too was equally effective as Anosom 2ml l-1 in its efficacy, the population of the pest being reduced by 40 per cent. The extent of reduction in the pest population in carbaryl 0.15%, B. bassiana 2g l-1 and B. thuringiensis 2g l-1 treatments was 35, 35 and 33 per cent, respectively. More than 50 per cent reduction in the number of fruits damaged was recorded B. bassiana 2g l-1, flubendiamide 0.004%, B. thuringiensis 2g l-1 and spinosad 0.015% treatments. Anosom 2ml l-1 and annona seed extract 5% resulted in more than 40 per cent reduction in the fruit damage. Carbaryl 0.15% registered 39 per cent reduction in the fruit damage. All the treatments increased the yield of the crop significantly, the extent of yield increase ranging from 36 to 44 per cent in the insecticide, 39 to 41 per cent in the botanical and 26 to 39 per cent in the microbial treatments. Based on the results of the study, destruction of the weed and other volunteer host plants and early detection of the pest and its management with either the botanicals or microbials would be a viable option for controlling the pest. The safer insecticides flubendiamide 0.004% or spinosad 0.015% could be used when there is a substantial increase in the pest population.